Innovation of e-procurement: a case study - Foulds, L.; West, Martin (InderScience Publishers, 2006)
Many organisations are increasingly searching for innovative processes and methods to achieve competitive advantage and to more fully take advantage of what they have in order to improve. This article is an illustration of this in a particular company that investigated how to improve its e-procurement processes through business innovation. Specifically, it describes how the e-procurement process can be improved by taking advantage of informatin technology and systems for business innovation. We explore the possibility of applying Project management (PM) principles in order to enhance e-procurement. An understanding of the issues involved has been gained through a case study of Motorola China Inc., which has implemented a fully functional e-procurement process since 2002. Our findings establish the potential benefits, feasibility and utility of applying PM technology as a way of enhancing the existing e-procurement process. The case study also indicates that the existing planning, reporting and database management systems are likely to enhance the PM process.